Edukasi Literasi Keuangan bagi Guru SD dan SMP di Pematang Siantar melalui Sinergi dengan Bursa Efek Indonesia - Dian Zahra Syahfitri Lubis; Alvian Huda Pramana; Rilla Masyita; Siti Aisyah (LP3M IAIFA Kediri, 2025)
Financial literacy is an important skill that every individual must have, including teachers who play a strategic role in shaping a financially literate younger generation. However, many elementary and junior high school teachers still do not understand the basic concepts of financial literacy, especially those related to the capital market and investment. This study aims to analyze the role of capital market socialization in improving teachers' financial literacy through activities carried out by UINSU KKN students. The research method used a qualitative approach with data collection techniques through in-depth interviews and participatory observation of elementary and junior high school teachers who participated in the socialization. The results of the study show that capital market socialization has succeeded in broadening teachers' understanding of the importance of personal financial management, consistent saving, setting financial goals, and starting investments in legal and safe instruments such as mutual funds or sharia stocks. In addition to increasing knowledge, these activities also have a real impact on teachers' behavior and provide emotional and social benefits, where teachers feel valued and motivated to pass on their financial literacy knowledge to students. In conclusion, the capital market socialization conducted by UINSU KKN students plays a strategic role in shaping teachers as agents of change, increasing financial awareness, and encouraging the creation of an economically independent and intelligent generation.